Immunogenicity and safety of a new hexavalent rotavirus vaccine in Chinese infants: A randomized, double-blind, placebo-controlled phase 2 clinical trial - Zhi-Wei Wu; Fei Jin; Qing-Liang Li; Jia-Mei Gao; Hai-Song Zhou; Kai Duan; Zhao Gao; Yan Liu; Zhi-Yong Hao; Wei Chen; Yue-Yue Liu; Ge-Lin Xu; et al. (Human Vaccines & Immunotherapeutics, 2023)
Rotavirus remains a major cause of diarrhea among 5-y-old children, and vaccination is currently the most effective and economical measure. We conducted a randomized, double-blind, placebo-controlled phase II clinical trial designed to determine the dosage, immunogenicity, and safety profile of a novel hexavalent rotavirus vaccine. In total, 480 eligible healthy infants, who were 6–12 weeks of age at the time of randomization were randomly allocated (1:1:1) to receive 105.5 focus-forming unit (FFU) or 106.5FFU of vaccine or placebo on a 0, 28 and 56-d schedule. Blood samples were collected 28 d after the third dose to assess rotavirus immunoglobulin A (IgA) antibody levels. Adverse events (AEs) up to 28 d after each dose and serious adverse events (SAEs) up to 6 months after the third dose were recorded as safety measurements. The anti-rotavirus IgA seroconversion rate of the vaccine groups reached more than 70.00%, ranging from 74.63% to 76.87%. The postdose 3 (PD3) geometric mean concentrations (GMCs) of anti-rotavirus IgA among vaccine recipients ranged from 76.97 U/ml to 84.46 U/ml. At least one solicited AE was recorded in 114 infants (71.25%) in the high-dose vaccine group, 106 infants (66.25%) in the low-dose vaccine group and 104 infants (65.00%) in the placebo group. The most frequently solicited AE was fever. The novel oral hexavalent rotavirus vaccine was safe and immunogenic in infants support the conclusion to advance the candidate vaccine for phase 3 efficacy trials.